Answer:
c - 5 x + 13 x ² + 4 x ³
Explanation:
First, we have to evaluate the function at x = 0. Like " f (x) = 4 x ³ + 13 x ² - 5 x + c.
Then we have to differentiate like " f (0) = c.
After that, we evaluate the function again at x = 0. Like this "f ' (x) = 12 x ² + 26 x - 5.
Then, we differentiate again like " f ' (0) = -5
We have to keep repeating and evaluate the function at x = 0 like this " f " (x) = 24 x + 26"
We have to repeat and differentiate like this " f " (0) = 26.
Now, we substitute x = 0, like this "f ⁽³⁾(x) = 24
After that, we have to list the values we found "f ⁽³⁾(x) = 24"
Use the definition "f (0) = c , f ' (0) = - 5 , f " (0) = 26 , f ⁽³⁾ (0) = 24
Simplify like "c - 5 x + 26 x x ² + 24
--- ---
2 ! 3 ! x x ³
Then, your solution is c - 5 x + 13 x ² + 4 x ³!
Hope this helps! :)